Pengaruh Psikoedukasi terhadap Pengetahuan dan Beban Caregiver Skizofrenia - Nelia Afriyeni; Sartana Sartana (Universitas Andalas, 2020)
The research aim to see does psychoeducation given to caregivers will affect knowledge and caregiver’s burden. The research approach is quasi-experimental with a nonrandomized pretest- posttest control group design. The research participants were 17 people (9 in the experimental & 8 in the control). The given of psychoeducation carried out in experimental group, while control group in the form of sharing sessions. Both groups given pretest & posttest. Caregiver knowledge measured using Schizophrenia Knowledge Scale, while caregiver burden measured using Zarith Burden Interview (ZBI). Data obtained were processed using Mann-Whitney U test to know the level of treatment effect using the effect size. The results showed difference in the increase of knowledge about schizophrenia and also a decrease in the burden felt by the schizophrenia’s caregiver between the experimental & the control groups. Thus, the results of the research indicate the given of psychoeducation is proven to increase the caregiver's knowledge, and to reduce the burden felt by schizophrenia's caregiver. Based on the calculation result on the effect size obtained a value of 0.49 for the knowledge and 0.69 for the burden. Keywords: burden, caregiver, knowledge, psychoeducation, schizophrenia